Literature Review: Positive Impact of Training in Improving Nursing Care Quality Competencies - Yustina Yustina; Dyah Wiji Puspita Sari; Iwan Ardian; Muh. Abdurrouf (GLOBAL HEALTH SCIENCE GROUP, 2025)
Quality nursing care is highly dependent on the competence of nurses in providing care in accordance with professional standards. Many nurses still face challenges in improving their skills and knowledge along with the development of science and technology in the health sector. Training is one of the effective methods to improve competence and quality of nursing care. Objective: This study aims to analyze the positive impact of training in improving nurses' competence in providing quality nursing care. Methods: This study used a review of national and international literature published between 2020-2024 and freely available. A systematic search using Google Scholar, PubMed, and SciSpace databases, using the keywords: Competency, Quality of nursing care, Training, with the PCC approach. The article selection process used PRISMA which was then subjected to critical appraisal. The process of searching and screening journal articles began by identifying 5,940 articles from the three main databases. After duplication elimination, 5,040 articles remained. Screening was conducted, removing 845 articles that did not meet the criteria, leaving 55 articles. Next, selection based on inclusion and exclusion criteria eliminated 44 articles, leaving only 11 articles eligible for further review and review. Results: The results showed that there was a significant improvement in the aspects of knowledge, skills, and attitudes of nurses after attending the training. Conclusion: training has a significant positive impact in improving nurses' competence and the quality of nursing care.